PENGARUH KONSERVATISME AKUNTANSI DAN KEPEMILIKAN MANAJERIAL TERHADAP ASIMETRI INFORMASI PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FARMASI PERIODE 2019-2021 - Alansori, Apip; Kustina, Nani; Alfiana, Nanda (Institut Rahmaniyah Sekayu, 2024)
This study aims to examine the effect of accounting conservatism and managerial ownershipon information asymetry. This type of research is quantitative research. The population in this study are pharmaceutical subsector companies listed on the Indonesia Stock Exchange (IDX) during 2019-2021. In this study, a purposive sampling methodwas used, namely the selection of samples with predetermined criteria. Based on the purposive sampling method,the samples obtained were 27 samples from 9 pharmaceutical sub-sector companies. The analytical method used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing by processing the data using SPSS version 25. The results of this study indicate that the accounting conservatism variable has no significant effect on information asymmetry and the managerial ownership variable has a significant effect on infprmation asymmetry. As well as the results pf simultaneous testing indicate that accounting conservatism and managerial ownership variables effect information asymmetry.